The South China Sea disputes and law of the sea - CIL Roundtable on the South China Sea, International Law and UNCLOS (2013 : Singapore); Jayakumar, S.; Koh, Tommy T. B. (Tommy Thong Bee), 1937-; Beckman, Robert C. (Law teacher); National University of Singapore. Centre for International Law (Cheltenham, UK : Edward Elgar, 2014)
This book explores in detail the application of specific provisions of the UNCLOS and how the framework of international law applies to the South China Sea.
Introduction / S. Jayakumar, Tommy Koh and Robert Beckman -- Offshore features subject to claims of sovereignty / Bernard H Oxman -- Defining the'boundary' between land and sea: territorial sea baselines in the South China Sea / Clive Schofield -- Maritime zones from islands and rocks / Clive R Symmons -- Maritime delimination and offshore features / Tullio Treves -- Rights and jurisdiction over resources in the South China Sea: UNCLOS and the'nine-dash line' / Ted L McDorman -- Do the coastal states in the South China Sea have a continental shelf beyond 200 nautical miles? / Alex Oude Elferink -- Rights and obligations in areas of overlapping maritime claims / David Anderson and Youri van Logchem -- UNCLOS Part XV and the South China Sea / Robert Beckman.
Papers based on CIL Roundtable on the South China Sea, International Law and UNCLOS held in Singapore, 27-28 June, 2013.
Includes bibliographical references and index.
Keywords: United Nations Convention on the Law of the Sea -- (1982 December 10) -- Congresses; Law of the sea -- South China Sea -- Congresses; South China Sea -- International status -- Congresses